#### Answer

a) $(2,-1)$
b) When we solve the system using the elimination method, it becomes easy because $2y$ is common to both equations.

#### Work Step by Step

a) Rewrite the first equation as: $2y=4-3x$
or, $y=2-\dfrac{3x}{2}$
Therefore, the first equation yields:
$5x-2(2-\dfrac{3x}{2}) =12 \implies x=2$
Substitute the value of $x$ into the first equation to get the value of $y$.
Thus, $y=2-\dfrac{3(2)}{2} \implies y=-1$
So, the solution is $(2,-1)$
b) When we solve the system using the elimination method, it becomes easy because $2y$ is common to both equations.